The role of UPR‐related long noncoding RNAs in development of endocrine resistance in breast cancer - Liu, Wen; Gupta, Sahil; Gupta, Sanjeev (International journal of cancer, 2025)
Breast cancer patients who express estrogen receptor α (ER) typically receive endocrine therapy as a first‐line treatment. Most ER‐positive breast cancer patients initially respond to endocrine therapy, but up to 40% of patients develop resistance over time, and the main mechanism is aberrant activation of ER signaling pathways. Recent research has shown that cancer's uncontrolled proliferative capacity and a hostile microenvironment can induce endoplasmic reticulum (EnR) stress and trigger unfolded protein response (UPR), which plays a crucial role in determining cell fate. Furthermore, increasing evidence suggests that noncoding ribonucleic acids (RNAs), which are involved during the crosstalk between the UPR and ER signaling pathways, play an essential role in endocrine resistance. In this review, we provide an overview of long noncoding RNA (lncRNA) that is involved both in endocrine resistance and UPR. We provide new insights into potential treatment strategies to overcome endocrine resistance in ER‐positive breast cancer patients by targeting the lncRNA that plays key roles in endocrine resistance and UPR signaling. Finally, we discuss the current state and future directions for targeting lncRNAs to improve clinical outcomes in endocrine‐resistant breast cancer patients.